2016
DOI: 10.3103/s0095452716030117
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substances with cryoprotective properties on surface marker CD44 in human erythrocytes

Abstract: The changes in surface marker CD44 in human erythrocytes exposed to cryoprotective media, as well as the impact of oxidative modification of membrane-cytoskeleton proteins on the CD44 characteristics under the changed physicochemical parameters of the cellular environment, were investigated in this study. Prolonged exposure of glycerol, DMSO, sucrose, and PEG-1500 caused a decrease in CD44 expression level and in amount of CD44-positive cells. That may reflect subtle rearrangements in the system of protein-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…This may be due to changes in the protein-protein interactions in the cell membrane. In drug-loaded RBCs, CD44 plays a key role in maintaining the stability of the cell membrane 166 . Damage to the cell membrane can affect the ability of RBCs to bind to other cells and tissues, leading to problems such as anemia, rheumatoid arthritis, and multiple sclerosis.…”
Section: The Factors Affecting the Aging And Clearance Of Rbcsmentioning
confidence: 99%
“…This may be due to changes in the protein-protein interactions in the cell membrane. In drug-loaded RBCs, CD44 plays a key role in maintaining the stability of the cell membrane 166 . Damage to the cell membrane can affect the ability of RBCs to bind to other cells and tissues, leading to problems such as anemia, rheumatoid arthritis, and multiple sclerosis.…”
Section: The Factors Affecting the Aging And Clearance Of Rbcsmentioning
confidence: 99%
“…This assumption is based on the fact that MCC proteins play an important role in maintaining the unique shape of cells and ensuring mechanical stability and deformability of erythrocytes in the bloodstream [5]. In addition, it was previously found that in erythrocytes under the influence of PEG [6] and freeze-thawing processes [7] there is a significant decrease in the expression of the surface marker CD44, which may be induced by disturbances of intermolecular interactions in MCC.…”
Section: Introductionmentioning
confidence: 99%
“…Воздействие ДМСО на клетку имеет несколько точек приложенияэто изменение проницаемости мембран для макромолекул, изменение осмотического потенциала цитоплазмы, ремоделирование молекул биополимеров, в связи с чем он имеет широкое распространение в медицине и биологии, в том числе в качестве криопротектора. В многочисленных работах установлена зависимость характера воздействия ДМСО на клетку в зависимости от его концентрации [1][2][3]. При этом порог чувствительности к воздействию может быть различным для разных клеточных систем, в зависимости от их метаболических особенностей.…”
unclassified